In vitro evaluation of acellular collagen matrices derived from porcine pericardium: Influence of the sterilization method on its biological properties - De Grandis, Rone Aparecido [UNESP] (2021)
The aim of this study were characterize acellular collagen matrices derived from porcine pericardium (PP) and to evaluate their properties after sterilization by ethylene oxide and gamma ray. PP matrices were subjected to alkaline hydrolysis (AH), and samples were characterized for biological stability, membrane thickness measurements, differential scanning calorimetry (DSC) and scanning electron microscopy (SEM). Subsequently, the matrices were frozen, lyophilized and sterilized by ethylene oxide or gamma radiation. For in vitro assays, CHO-K1 cell culture was used and evaluated for cytotoxicity, clonogenic survival assay, genotoxicity and mutagenicity. Analysis of variance (ANOVA) was used, followed by Dunnett’s post-test, with a significance level of 5%. After AH, there was no significant change in matrix thickness. The relative biodegradability of the material after implantation was observed. Morphology and dimensions had small changes after AH. As for cell viability, none of the tested matrices showed a statistically significant difference (p > 0.05; Dunnett) regardless of the sterilization method. Furthermore, it was found that PP matrices did not interfere with the proliferation capacity of CHO-K1 cells (p > 0.05; Dunnett). As for genotoxicity, when sterilized with ethylene oxide (NP, P12 and P24), it showed genotoxic potential, but it was not genotoxic when sterilized by gamma radiation. No mutagenic effects were observed in either group. PP-derived collagen matrices hydrolyzed at different times were not cytotoxic. It is concluded that the best method of sterilization is through gamma radiation, since no significant changes were observed in the properties of the PP matrices.